A Systematic Study of the Influence of Electrolyte Ions on the Electrode Activity. Issue 1 (14th January 2022) - Ding, Xing; Scieszka, Daniel; Watzele, Sebastian; Xue, Song; Garlyyev, Batyr; Haid, Richard W.; Bandarenka, Aliaksandr S.
Abstract: Efficient electrocatalysis is most likely an answer to recent energy related challenges. Countless studies have been trying to find the links between the electrode/electrolyte interface structure, its composition, and the resulting activity in order to improve the performance of numerous devices, such as electrolyzers, fuel cells, and certain types of batteries. However, this scientific field currently meets serious complications associated with the prediction and explanation of an unexpected influence of seemingly inert electrolyte components on the observed activity. Herein, we investigate various electrocatalytic systems using a unique laser‐induced current transient technique to answer a long‐lasting fundamental question: How can "inert" electrolytes change the activity so drastically? Different metal electrodes in contact with various aqueous solutions and two energy important reactions were used as model systems. We experimentally determine the potential of maximum entropy of the electrodes and find the connections between its position and the electrocatalytic performance. Abstract : Not so inert : By identifying the potential of maximum entropy (PME) with the laser‐induced current transient technique, the fundamental connections between the PME and the electrocatalytic performance were obtained. The presented results confirm the expectation that the closer the PME to the thermodynamic equilibrium potential of an electrocatalytic reaction is, the faster the respective reaction should be. Hence, it is believed that the presented approach can be a powerful tool for studying the mechanism of the interfacial processes and further optimizing the electrochemical system.